Rapid Effect of Nicotine Intake on Neuroplasticity in Non-Smoking Humans - Grundey, Jessica; Thirugnanasambandam, Nivethida; Kaminsky, Kim; Drees, Anne; Skwirba, Angela; Lang, Nicolas; Paulus, Walter; Nitsche, Michael A. (Frontiers in Pharmacology, 2012)
In various studies nicotine has been shown to alter cognitive functions in non-smoking subjects, which might be due to nicotine-generated modulation of cortical functions, excitability and activity, as mainly described in animal experiments. In non-smoking humans application of nicotine for hours via nicotine patch abolishes inhibitory plasticity both after cathodal transcranial direct current stimulation (tDCS) or paired associative stimulation (PAS-10). Excitatory anodal tDCS after-effects were reduced whereas excitatory PAS-25 was prolonged. These results are compatible with the view that prolonged nicotine administration facilitates focal synapse-specific excitatory plasticity as induced with excitatory PAS as focusing effect. However, since nicotine receptors undergo rapid adaption processes within minutes, the results cannot distinguish between an impact of the substance alone or a compensatory receptor adaption. Thus in the present study we replicated the experiments however using nicotine spray, which enhances blood concentration of nicotine within minutes. 48 non-smokers received nicotine spray respectively placebo spray combined with either facilitatory or inhibitory tDCS or PAS. Corticospinal excitability was monitored via motor-evoked potentials elicited by transcranial magnetic stimulation (TMS). Nicotine spray abolished all types of plasticity except synapse-unspecific non-focal tDCS-derived excitability reduction, which was delayed and also weakened. Thus, the effects of short-term nicotine application differ from those of prolonged nicotine application, which might be due to missing adaptive nicotinic receptor alterations. These results enhance our knowledge about the dynamic impact of nicotine on plasticity, which might be relevant to its heterogeneous effect on cognition.